Implementasi Metode Pembiasaan dalam Pembelajaran IPS untuk Menumbuhkan Sikap Disiplin Siswa Sekolah Dasar - Yusuf Rendi Wibowo; Fatonah Salfadilah (JURNAL DIKDAS, 2026)
This study aims to analyze the implementation of habituation methods in social studies (IPS) learning to foster student discipline in elementary schools. Conducted as a case study at SDN 1 Way Mili, this research employed qualitative methods involving observation, interviews, and documentation. The findings indicate that the systematic and consistent implementation of the habituation method, through phases such as preparation, initial application, habituation, and evaluation, significantly improves student discipline. The students demonstrated better adherence to class rules, punctuality in completing assignments, and overall organization. Reinforcement techniques, such as positive feedback and recognition, played a crucial role in strengthening disciplined behavior, making it a habit in students' daily lives both at school and beyond. The study concludes that the habituation method is effective in fostering discipline and recommends its broader application in other subjects, along with consistent collaboration among teachers and school programs to support character building.